2021
DOI: 10.3389/fmars.2021.697424
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Quantification of Micro(Nano)Plastics and Plastic Additives in the Seawater of Mar Menor Lagoon

Abstract: In this work a suspect-screening approach was employed to assess the polymers and plastic additives of micro(nano)plastics (NPL/MPLs) of size ranges from the nm range to 20 μm present in seawater from the top 5 cm of the Mar Menor lagoon during two sampling campaigns (summer and winter), as well of other potentially adsorbed compounds onto the plastic particles surfaces and suspended material. The identification of NPL/MPLs has been based on characteristic Kendrick Mass Defect analysis for each polymer type in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 57 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…Regarding the frequency of sampling, the reviewed studies sampled only once (a single monitoring campaign), except for three studies that performed multiple monitoring campaigns (two [ 42 , 63 ] and five [ 56 ]), and one paper that collected samples from 1984 to 2008 (roughly every 5 years) and demonstrated that the concentrations of all detected persistent organic pollutants (POPs) decreased over the last two decades [ 31 ]. The results obtained from a single monitoring campaign could produce relatively large errors in the estimation of the actual pollution level in the MPs because the findings can be influenced by several variables, such as the sample size and sampling time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the frequency of sampling, the reviewed studies sampled only once (a single monitoring campaign), except for three studies that performed multiple monitoring campaigns (two [ 42 , 63 ] and five [ 56 ]), and one paper that collected samples from 1984 to 2008 (roughly every 5 years) and demonstrated that the concentrations of all detected persistent organic pollutants (POPs) decreased over the last two decades [ 31 ]. The results obtained from a single monitoring campaign could produce relatively large errors in the estimation of the actual pollution level in the MPs because the findings can be influenced by several variables, such as the sample size and sampling time.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 60 original articles were read in full and then 20 papers were removed with reason, as reported in Table S1 . In total, 40 studies met the selection criteria and were included in this review [ 23 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ] ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Quo Vadis? In environmental monitoring (e.g., air, water, soil), HRMS-based analyses have been rapidly expanding over the past decade. , Platforms and workflows are being repurposed to target new and more pertinent chemical classes, as reflected in the Toxic Substances Control Act (TSCA) Inventory or more selective databases. , These new compounds and substances include many contaminants of emerging concern (CEC), and are wide-ranging by structure, use, and toxicity, spanning PFAS, phthalates, pharmaceuticals, UVCB substances (short for “unknown or variable composition, complex reaction products or of biological materials”) and microplastics, among numerous others. Recent case studies to discover causative toxicants provide clues not only for profiling actual exposure occurrences and risk assessment but impart insights into the methodological design for HRMS-based exposomics altogether.…”
Section: Toward Merging Targeted and Non-targeted Approachesmentioning
confidence: 99%